Biochemical investigations of biogroups and subspecies of Morganella morganii. - Janda, J M (1996)
We determined the subspecies and biogroup designations for 73 strains of Morganella morganii principally recovered from routine clinical specimens. On the basis of trehalose fermentation, 90% of all strains were identified as M. morganii subsp. morganii (trehalose negative), while the remaining 10% were designated M. morganii subsp. sibonii (trehalose positive). Using three tests (ornithine decarboxylase [ODC] and lysine decarboxylase [LDC] activities and susceptibility to tetracycline), we determined the biogroup designations for these 73 strains. Four of the seven recognized biogroups within the genus Morganella were found in the study, with biogroup A (ODC positive [ODC+], LDC negative [LDC-]) predominating (78%); all M. morganii subsp. sibonii strains were found to belong to biogroup G (ODC+, LDC-). Rapid glycerol fermentation (24 h) was linked to nonmotility and biogroup B strains (ODC+, LDC+). LDC activity but not tetracycline resistance appeared to be associated with the possession of a 40- to 45-MDa plasmid. The use of three commercial systems (API ZYM, API 50 CH, and Biolog GN) failed to detect any new biochemical tests useful for subspecies identification, with the possible exception of L-phenylalanine utilization as a sole carbon source in the Biolog GN system. No Morganella strain was found to invade either HEp-2 or Vero cell lines, but four of seven M. morganii subsp. morganii strains were cytotoxic on sheets of both cells. This cytotoxic activity appeared to correlate with the rapid expression of beta-hemolytic activity.